Pengaruh Kepemilikan Manajerial, Risiko Litigasi dan Leverage terhadap Konservatisme Akuntansi dengan Financial Distress sebagai Variabel Moderating - Elvi Rahmi; Niswah Baroroh (Politeknik Ganesha Medan, 2022)
Accounting conservatism is an attitude of prudence in responding to uncertainties in the future by recognizing expenses and liabilities as soon as possible, but only recognizing income and assets when they are sure they will be received. Accounting conservatism in Indonesia is still very low. There are still some companies that have not applied the accounting conservatism method. In this study, the purpose is to investigate the influence of management ownership, litigation risk, and leverage on accounting conservatism using financial distress as the moderating variable. The population was picked as many as 26 manufacturing enterprises listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 timeframe, and 72 samples were gathered by purposive sampling approach. Descriptive analysis and regression analysis were utilized to assess the data via a moderating test of the difference in absolute values. The findings demonstrate that management ownership and litigation risk do not have a considerable influence, whereas leverage has a big impact on accounting conservatism. Financial distress is not able to moderate considerably in order to affect the three factors on accounting conservatism. Therefore, additional study is required to broaden the factors so that the findings obtained are more correct. Suggestions from this study, the company is expected to improve the principle of accounting conservatism to reduce the asymmetry between shareholders or investors and creditors.